The Contribution of Optical Coherence Tomography in Neuromyelitis Optica Spectrum Disorders - Mateo, Javier; Esteban, Olivia; Martínez, Mireya; Grzybowski, Andrzej; Ascaso, Francisco Javier (Frontiers in Neurology, 2017)
Neuromyelitis optica spectrum disorders (NMOSD) comprises a group of central nervous system disorders of inflammatory autoimmune origin that mainly affect the optic nerves and the spinal cord and can cause severe visual and general disability. The clinical signs are similar to those of multiple sclerosis (MS), with the result that it is often difficult to differentiate between the two, thus leading to misdiagnosis. As the treatment and prognosis of NMOSD and MS are different, it is important to make an accurate and early diagnosis of NMOSD. Optical coherence tomography (OCT) is a non-invasive technique that enables a quantitative study of the changes that the optic nerve and the macula undergo in several neurodegenerative diseases. Many studies have shown that some of these changes, such as retinal nerve fiber layer thinning or microcystic macular edema, can be related to alterations in the brain due to neurodegenerative disorders. The purpose of this mini-review is to show how OCT can be useful for the diagnosis of NMOSD and follow-up of affected patients, as well as for the differential diagnosis with MS.